2017
DOI: 10.1111/jcmm.13132
|View full text |Cite
|
Sign up to set email alerts
|

GC‐MS metabolomics‐based approach for the identification of a potential VOC‐biomarker panel in the urine of renal cell carcinoma patients

Abstract: The analysis of volatile organic compounds (VOCs) emanating from biological samples appears as one of the most promising approaches in metabolomics for the study of diseases, namely cancer. In fact, it offers advantages, such as non‐invasiveness and robustness for high‐throughput applications. The purpose of this work was to study the urinary volatile metabolic profile of patients with renal cell carcinoma (RCC) (n = 30) and controls (n = 37) with the aim of identifying a potential specific urinary volatile pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 59 publications
(84 reference statements)
2
43
0
Order By: Relevance
“…Gas chromatography mass spectrometry (GC–MS) is a platform of choice for qualitative and quantitative analysis of OAs in laboratory settings (Bouatra et al, ), because of its advantages including high sensitivity, peak resolution and reproducibility. This technology has been applied to determine changes in global metabolite profiling in urine from patients with prostate (Lima et al, ), bladder (Zhou et al, ) and renal cancers (Monteiro et al, ). Several important observations regarding altered levels of OAs have recently been obtained from GC–MS.…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatography mass spectrometry (GC–MS) is a platform of choice for qualitative and quantitative analysis of OAs in laboratory settings (Bouatra et al, ), because of its advantages including high sensitivity, peak resolution and reproducibility. This technology has been applied to determine changes in global metabolite profiling in urine from patients with prostate (Lima et al, ), bladder (Zhou et al, ) and renal cancers (Monteiro et al, ). Several important observations regarding altered levels of OAs have recently been obtained from GC–MS.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that human body emits a wide array of volatile organic compounds (VOCs), both odorous and non-odorous, depending on individual background [33]. These VOCs are emitted throughout the body, including breath, blood and urine [34,35]. According to analysis of VOCs, different volatile patterns have been correlated with a variety of diseases including cancers [14,33,36,37], which dogs can be trained to detect.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological assessment uncovered insignificant ceaseless renal ailment. However, pee result was common, the essential unfavorable impacts identified was ascending in an adjustment in hyaline bead in male rodents and harm of kidney in the female rodents led to cell toxicity [28,29].…”
Section: Petroleum Hydrocarbon On Renal Systemmentioning
confidence: 99%